Distributed System Reliability in Intelligence Information System - Achkoski, Jugoslav; Trajkovik, Vladimir (Business Informatics, 2014)
This paper presents the model of Intelligence Information System (IIS) based on a Service-Oriented Architecture. In this paper we propose the new service’s model, based on the Intelligence cycle and other systems which are necessary for gathering intelligence information and data. The paper is mostly focused on the system architecture and services design as a mainstream for definition of the services. Furthermore, additional attention is dedicated on the Distributed System Reliability (DSR)
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 9-23
Keywords: Service-Oriented Architecture; service design; Distributed System Reliability (DSR); Intelligence Information System; system’s architecture; architektura zorientowana na usługi; projektowanie usług; niezawodność systemu rozproszonego; System Informacji Wywiadu; architektura systemu